Un’iniziativa tedesca per la psicoterapia delle psicosi: la DDPP. Intervista a Dorothea von Haebler - von Haebler, Dorothea; Homberg, Annelore; Arcà, Lucia (Il sogno della farfalla, 2013)
In this interview, Dorothea von Haebler, Oberärztin at the Psychiatric Department of the University Charité in Berlin, describes the setting up, the objectives and the initiatives of the Dachverband deutschsprachiger Psychosentherapie (“Confederation for the psychotherapy of psychosis in German speaking countries”, DDPP) of which she is president. The DDPP aims to give people suffering from psychosis access to psychotherapy, given that the German health insurance fund covers only psychopharmacological treatments. Moreover, she describes how her personal interest in the psychotherapy of psychoses started, the books which have influenced her most and comments on the renewed interest in this field after decades characterized by the predominance of biological psychiatry.